Clínica, Cirurgia e Anestesiologia de Pequenos Animais. - Cappellesso, Millena da Silva Vieira (Universidade Federal do Tocantins, 2023)
The traineeship was conducted at the Veterinary University Hospital of School of Veterinary Medicine and Zootecnia of Federal University of Tocantins (HVU-EMVZ-UFT), from October 21th to December 20th 2013, totaling 560 hours. In this period 108 clinical cases were treated. Trainees were required to follow the monitor residents in attendance, performing anamnesis, physical examination, collection of biological samples, also monitor surgical procedures, from preoperative until release the patient. This report aims to describe the activities performed at the traineeship, a literature review about pyometra, abording renal complications related with pyometra and describe one clinical case report.